Navigating the digital landscape: A conceptual framework linking digital literacy, stress reduction and well-being outcomes - Amram, Nor Razuana; Hashim , Muhammad Asyraaf; Rosli, Nuraina Nadiah; Saleh, Nur Fathia; Shariff, Qatrunnisa; Awang Besar, Nazirul Mubin (International Journal of Accounting, Finance and Business, 2026)
In an era characterized by unprecedented digital transformation, individuals are confronted with the paradoxical challenge of harnessing technology's. This conceptual paper aims to review a comprehensive framework that elucidates the relationships among digital literacy, well-being outcomes, and stress reduction. In reviewing recent studies conducted between 2023 and 2025, this research finds that there are two related paths through which digital literacy shapes health: Relationship between digital literacy and stress reduction and Digital literacy's direct and indirect effects on well-being. The critical theoretical significance of the developed integrated framework includes its ability to clearly distinguish between digital competency and digital dependency, where focusing on emotional regulation. There are implications on how this integrated framework should be supported across education sectors, healthcare, and public policies, where digital literacy should not only include technical competencies but also emotional regulation and health-related competencies.